Electrochemical and magnetic properties of α-MnO2:Dy nanorods - Gangwar D.; Rath C. (My University, 2025)
A facile hydrothermal technique with optimized condition used to synthesize single crystalline, α-MnO2 and α-MnO2:Dy nanorods of diameter 40 and 20 nm, respectively. We observe two fold magnitude higher specific capacitance (94 F g−1 at a scan rate of 10 mV/sec) in α-MnO2:Dy than that of α-MnO2 nanorods. X-ray diffraction (XRD) patterns while confirm the tetragonal structure in both compounds, decrease in crystallinity as well as aspect ratio of nanorods in α-MnO2:Dy contribute towards high capacitance. A decrease in Neel temperature (TN) from 24.5 K in bulk to 18 K in α-MnO2 nanorods further decreases to 11 K in α-MnO2:Dy nanorods. Addition to TN at 11 K, another magnetic anomaly at 4 K indicates Dy-Dy interaction. Although Dy incorporation enhances the antiferromagnetic strength as indicated from high Curie-Weiss temperature (θcw), exchange bias field significantly decreases and spin-glass behaviour is absent unlike in bare α-MnO2. Such magnetic features are well explained on the basis of core shell structure of nanorods where core is contributed by antiferromagnetic frozen spins and rotatable spins are contributed towards the surface. The competition between core and surface spins depending on the size of nanorods thus decides the spin-glass behaviour, EB field observed in these nanorods. Change in exchange bias field with consecutive cycles showing the training effect has been discussed after fitting with phenomenological models like Power law and multiple exponent function. © 2019 Elsevier B.V.